Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Pengungkapan CSR Dan GCG Sebagai Variabel Pemoderasi - Auliyah Palupi Putri Indra Sari; Ronny Malavia Mardani; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACK The purpose of this reserach is: 1) To analysis the financial performance effect the value of5the company from Consumer Goods di BEI periode 2013-2016. 2) To analysis Corporate Social Responsibility moderation of financial performance relationships to the value of5the company. 3) To analysis Good Corporate Governance moderation of financial performance relationship to the value of the company. This reserach using secondary data, and sample taking in the reseach5is using method Purposive Sampling by sampling 67 during the periode 2013-2016.The result of this reserach show that: 1) ROA have a significant positive effect on company Value. 2) Based on the result of the analysis can be provade that also CSR be able to moderation relationship ROA with company Value. 3) Based on the result of the analysis that also GCG be able to moderation relationship between ROA with company Value. This shows that Financial Performance the effect on company Value with disclosure Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) as a moderation variable.Keyword: Financial Performance, Company Value, Corporate Social Responsibility (CSR), Corporate Governance (GCG).